Cultural Competence of Professionals Working With Unaccompanied Minors: Addressing Empathy by a Shared Narrative - Radjack, Rahmeth; Touhami, Fatima; Woestelandt, Laure; Minassian, Sevan; Mouchenik, Yoram; Lachal, Jonathan; Moro, Marie Rose (Frontiers in Psychiatry, 2020)
Background The number of migrant youth traveling without parents continues to rise in Europe and North America. Some of t hem leave their home countries on their own and find themselves in a new country, separated from their family and cut off from their cultural roots. Besides those who leave to study, work, and pursue a better life, others are escaping war-torn countries. They need adequate social, educational, and therapeutic spaces, where they can feel entitled to speak. Social workers often ask about how they can understand these young people better so that they can provide them with better care (cope with their trauma and suspicion, deal with the cultural distance between the adolescents and their social workers, etc). Aim At Cochin Hospital in Paris, we led a participative action-research program to transmit cultural competence to social workers who provide care for these youth. The aim was to develop an approach to help these young migrants to share their representations about themselves and to train these social workers to encourage this sharing in a culturally sensitive manner. Methods This study used a qualitative method that mixed narrative and transcultural approaches. Two researchers met each youth and social worker with an interpreter-cultural mediator three times (once a month) to assess changes in their relationships during the study. The youth were asked to bring three items of their choice, representing their past, present, and future. They could use their imagination and creativity. We also used the circle test described by Cottle for this purpose. We used a phenomenological approach to analyze the interviews. Results and Discussion This study included 29 young people from 13 different countries and 29 social workers. A transcultural approach appears to be a useful framework for reactivating their identity construction process. It promotes the emergence of cultural representations and takes their experiences before, during, and after migration into account. We assisted them in developing their ability to produce a thorough narrative of their bicultural adolescences and simultaneously helped their social workers to develop their cultural competence. Conclusion Together, a transcultural approach and methods stimulating the production of narrative are relevant ways to help children to describe their representations of themselves, especially those who have learned to protect themselves by remaining silent. This protocol could be useful for both preventive action and therapy for psychotrauma.